Open Science Policies at the University of Edinburgh: Putting Policy into Practice - Tate, Dominic (Septentrio Conference Series, 2022)
Watch the VIDEO. Over the last 15 years, the policy environment has shaped the open access and open science agendas in UK higher education. This paper provides an overview of open science policies at a national level in the UK and at an institutional level within the University of Edinburgh, and assesses the efficacy of these policies in practice. This paper reviews what has worked well and why, describing the development of the University of Edinburgh’s current Research Publications & Copyright Policy (2021), which is a ‘rights-retention’ policy.